Pengaruh kesehatan keuangan dan ukuran perusahaan terhadap pertumbuhan laba - Agoestina Mappadang; Jusuf Luther Mappadang (Jurnal Riset Manajemen dan Bisnis, 2022)
This examination was led to analyze the financial health with the factor Current Proportion, Obligation to Value Proportion, Absolute Resource Turnover, and Firm Size on Benefit Development. This examination utilizes populace and test organizations in the shopper merchandise industry area which are recorded on the Indonesia Stock Trade in 2017-2019 and there are 19 organizations that meet the standards. The logical device utilized is different straight relapse examination. The example is dictated by purposive inspecting method to get an agent test as per determined models. In view of the aftereffects of the examination note that All out Resource Turnover and a critical impact on Benefit Development, while the Current Proportion, Obligation to Value Proportion, and Firm Size don't fundamentally impact Benefit Development. The size of the impact is 0.350 or 35%, while the leftover 65% is affected by different factors outside the investigation.